The Meaning of Khalaqa and Its Derivation in Surah Ar-Rum (Semantic Analysis of Toshihiko Izutsu) - Mislannada Fiddaraini; FNU Yusroh; Rika Astari; Abdul Mukhlis (IJAS: Indonesian Journal of Arabic Studies, 2022)
This study, entitled 'The Meaning of Khalaqa and its Derivation in Surah Ar-Rum (Semantic Study of Toshihiko Izutsu)' aims to describe the derivation of the word khalaqa in Surah Ar-Rum, explain its basic and relational meanings, explain the synchronic and diachronic words of khalaqa with a semantic perspective. Toshihiko Izutsu explains the world view of the derivation of the word khalaqa in Surah Ar-Rum. The method used in this research is descriptive with a qualitative approach. The type of research used is a literature study. The research design and framework are temporary because the research is open-ended, and this research is natural. The results of this study indicate that the form of the word khalaqa and its derivation in the surah Ar-Rum is found 10 times mentioned in 9 verses, some are in the form of file madi, fi'il mudari', and masdar. The basic meaning of each verse is creating, creation, and creation, and its relational meaning is related to the words Allah, Allah, Yabda’u, Yu’iduhu, Fitrah, Yatafakkaru, as-Samawati wal-‘Ard, Alsinatikum wa Alwanikum, Azwaja, Turab, Basyar, Razaqakum, Yumitukum, yuhyikum, Da’fin quwwatan, Ma yasya’u and Wa min Ayatihi. The synchronic meaning is explained through the method of interpretation which comes from the explanations of the interpretations of Ibn Katsir, Al-Maragi, and Tafsir Al-Misbah. The diachronic meaning of the word khalaqa and its derivation consists of three phases, namely pre-Qur'an, Qur'anic phase, and post-Qur'an. The resulting worldview can form the belief in the existence of Allah SWT with three types of components, namely a vertical relationship to Allah (hablun min Allah), a relationship to fellow humans (hablun minan-nas), and a close relationship to Allah through oneself (hablun binafsihi).تهدف هذه الدراسة المعنونة "معنى خلق واشتقاقها في سورة الروم (دراسة دلالية عند توشيهيكو إيزوتسو)" إلى وصف اشتقاق كلمة خلق في سورة الروم، وشرح معانيها الأساسية والعلائقية، وشرح المتزامن والكلمات المتزامنة للخلق من منظور دلالي: توشيهيكو إيزوتسو، ويشرح النظرة العالمية لاشتقاق كلمة خلق في سورة الروم.الطريقة المستخدمة في هذا البحث وصفية ذات منهج نوعي. نوع البحث المستخدم هو دراسة الأدب. تصميم البحث وإطاره مؤقتان لأن البحث مفتوح، وهذا البحث طبيعي.تشير نتائج هذه الدراسة إلى أن شكل كلمة خلق واشتقاقها في سورة الروم وجد 10 مرات المذكورة في 9 آيات بعضها على شكل الفعل الماضي، و المضارع، و المصدر. المعنى الأساسي لكل آية هو الخلق، والخالق، و المخلوق، ومعناه العلائقي مرتبط بكلمات الله، والفطرة، و من آياته والسماوات والأرض، والأزواج، والبشر و التراب و يبدأ و يعيد و رزق و يميت و يحيي و يتفكرو ما يشاء. ويفسر معنى التزامن من خلال منهج التفسير الذي يأتي من تفسير ابن كثير والمراغي وتفسير المصباح. يتكون المعنى التاريخي لكلمة الخلق واشتقاقها من ثلاث مراحل، وهي مرحلة ما قبل القرآن والمرحلة القرآنية وما بعد القرآن. يمكن لوجهة النظر الناتجة إلى العالم أن تكوِّن الإيمان بوجود الله سبحانه وتعالى بثلاثة أنواع من المكونات، وهي العلاقة الرأسية بالله (حبل من الله)، والعلاقة مع إخواننا من البشر (حبل من الناس)، والعلاقة الوثيقة بالله من خلال الذات. (حبل بنفسه).